1996
DOI: 10.3354/meps144185
|View full text |Cite
|
Sign up to set email alerts
|

Is hatching success of copepod eggs diatom density-dependent?

Abstract: Two species of diatoms, Phaeodactylurn tncornutum and Thalassiosira rotula, were fed to Calanus helgolandjcus females at concentrations varying between 10 and 106 cells ml-l. Their effects on the fecundity and hatching success of eggs were compared with those of the dinoflagellate diet Prorocentrum minl~nurn at 104 cells ml-' used as a control. Specific maximum fecundity was never reached with the diatom diets. The paradox is that fecundity and inhibition of hatching were diatom densitydependent, but varied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 18 publications
8
42
1
Order By: Relevance
“…Probably the strongest evidence from feeding studies that diatoms can have deleterious effects on egg production and hatchability was provided by Chaudron et al (1996). These authors found, in accordance with other studies, that negative effects on egg hatching in Calanus helgolandicus only occurred after several days of feeding on the examined diatoms.…”
supporting
confidence: 77%
“…Probably the strongest evidence from feeding studies that diatoms can have deleterious effects on egg production and hatchability was provided by Chaudron et al (1996). These authors found, in accordance with other studies, that negative effects on egg hatching in Calanus helgolandicus only occurred after several days of feeding on the examined diatoms.…”
supporting
confidence: 77%
“…The negative effect was weaker than starvation, but strong enough to make mixtures with adequate food supply of Rhodomonas and T. weissflogii inadequate. This contrasts with previous studies which used P. minimum as a control treatment against the negative impacts of diatoms as T. rotula on copepod hatching success (Chaudron et al 1996) and embryonic (Poulet et al 1994) as well as postembryonic development (Carotenuto et al 2002), and to reverse effects of diatom monodiets on copepod egg production (Poulet et al 2006). P. minimum Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…The mean minimum and maximum EPRs in Ebrié Lagoon (Pagano et al, 2004) were higher than those of other regions (Table 2). Copepod EPR is influenced by such endogenous factors as gonad development stages (Eisfeld and Niehoff, 2007), and by such dominant environmental factors as salinity (Castro-Longoria, 2003;Chinnery and Williams, 2004;Uriarte and Villate, 2006), photoperiod (Uye, 1980), turbulence (Kiørbe and Saiz, 1995;, temperature, and the abundance and quality of food (Poulet et al, 1995;Chaudron et al, 1996).…”
Section: Discussionmentioning
confidence: 99%